Are there benefits of social overinclusion? Behavioral and ERP effects in the Cyberball paradigm - Niedeggen, Michael; Sarauli, Natia; Cacciola, Santi; Weschke, Sarah (Frontiers in Human Neuroscience, 2014)
Social participation can be examined using the Cyberball paradigm, a virtual ball-tossing game. Reducing the involvement of the participant is supposed to activate a neural alarm system, and to threaten fundamental social needs. Our previous findings indicate that the latter process can be linked to an enhancement of the centro-parietal P3 amplitude, signalling a modulation of the subjective expectancy of involvement. A preceding more frontal ERP component, the P2, does not depend of the probability of involvement, but reflects the appraisal of social reward. In this experiment, we examined whether overinclusion of participants enhances the satisfaction of social needs, reduces the P3 amplitude correspondingly, and affects central reward processing. In the control condition, participants (n = 40) were included (two co-player, ball possession 33%), and overincluded (ball possession 46%) in the experimental condition. In a counterbalanced design, we also controlled for the order of conditions. As predicted, overinclusion increased the satisfaction of social needs, with exception of ‘self esteem’, and reduced the P3 amplitude. As for the frontal P2, overinclusion only enhanced the amplitudes if the less frequent involvement (condition: inclusion) was experienced previously. The behavioural and P3 data suggest that the feelings of social belonging, meaningful existence, and control are related to the subjective expectancy of social involvement, and can be described in terms of a linear continuum ranging from exclusion to overinclusion. In contrast, appraisal of social rewards does not depend on the probability of involvement.